1995
DOI: 10.1042/bj3080923
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the sizes of 53 introns and over 100 intronic sequences for the binding of common transcription factors in the human and mouse genes for type II procollagen (COL2A1)

Abstract: Over 11,000 bp of previously undefined sequences of the human COL2A1 gene were defined. The results made it possible to compare the intron structures of a highly complex gene from man and mouse. Surprisingly, the sizes of the 53 introns of the two genes were highly conserved with a mean difference of 13%. After alignment of the sequences, 69% of the intron sequences were identical. The introns contained consensus sequences for the binding of over 100 different transcription factors that were conserved in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…A sequence of 450 bp in the first intron of the rat type I1 collagen gene has been shown to increase the promoter activity several fold and to function as a tissue specific enhancer (Wang et al, 1991). Comparative sequence analyses of the rat, mouse, and human proal(I1) collagen promoter and intron 1 sequences have revealed marked conservation of the nucleotide sequence between the three species (Vikkula et al, 1992;Ala-Kokko et al, 1995) suggesting conservation of repulatorv seauences. cific enhancer in intron 1 comes from our earlier data.…”
Section: Regulation Of Procwl(i1) Collagen Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…A sequence of 450 bp in the first intron of the rat type I1 collagen gene has been shown to increase the promoter activity several fold and to function as a tissue specific enhancer (Wang et al, 1991). Comparative sequence analyses of the rat, mouse, and human proal(I1) collagen promoter and intron 1 sequences have revealed marked conservation of the nucleotide sequence between the three species (Vikkula et al, 1992;Ala-Kokko et al, 1995) suggesting conservation of repulatorv seauences. cific enhancer in intron 1 comes from our earlier data.…”
Section: Regulation Of Procwl(i1) Collagen Promotermentioning
confidence: 99%
“…Ala-Kokko et al (1991) have shown in a cell culture system that correct termination and 3'-processing of RNA transcripts of the gene also require sequences extending more than 80 bp downstream of the major polyadenylation signal. The entire 3'-untranslated domain of the mRNA is highly conserved between mammalian species (Metsaranta et al, 1991a;Ala-Kokko et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The Col2a1 gene contains many other potential transcription factor recognition motifs in addition to those for Sox proteins (Ala-Kokko et al, 1995;Ghayor et al, 2000;Huang et al, 2002;Kamachi et al, 1999;Murray et al, 2000). However, the identities most of the factors that bind to these motifs and their possible interactions with Sox proteins have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[6][7][8] Collagen XI is a heterotrimer of a1(XI), a2(XI) and a3(XI) chains encoded by three distinct genes; COL11A1, COL11A2 and COL2A1. [9][10][11] The COL2A1 gene also codes for the a1 chain of collagen II, but the a3(XI) chain undergoes more extensive post-translational modification than the a1(II) chain. 12 Collagens II and XI are present throughout Meckel's cartilage, which provides mechanical support for the developing mandible.…”
Section: Introductionmentioning
confidence: 99%